Nature relatedness, flow experience, and environmental behaviors in nature-based leisure activities - Akçakese, Andaç; Demirel, Mehmet; Yolcu, Alperen Fatih; Gümüş, Hüseyin; Ayhan, Cihan; Sarol, Halil; Işık, Özkan; Harmandar Demirel, Duygu; Stoica, Leonard (Frontiers in Psychology, 2024)
Through nature-based leisure activities, spending time in nature offers opportunities to reduce stress, relax the mind, and enhance feelings of well-being. Being aware of the benefits provided by these activities increases the nature relatedness, and during the time spent in nature, it enables experiencing positive and satisfying moments by entering into a state of flow. The concepts of nature-relatedness and flow experience represent psychological experiences and characteristics that play an important role in enhancing psychological well-being and life quality. In this study, based on structural equation models, the relationships among nature-relatedness, flow experience, and environmental behaviors were investigated. Data were collected from 379 individuals (212 male, 167 female) who regularly engage in nature-based leisure activities such as cycling, hiking, and fishing. The participants were predominantly male (55.9%) and aged 45 years and over (53.3%). Our analysis revealed that nature-relatedness significantly influences flow experience (R² = .505, p < 0.01), environmental behavior (R² = .108, p < 0.01), environmental sensitivity (R² = .137, p < 0.01), and communication with nature (R² = .200, p < 0.01). Specifically, nature-relatedness directly enhanced environmental sensitivity (.494 total effect), environmental behavior (.604 total effect), and communication with nature (.599 total effect) and did so both directly and indirectly through the mediation of flow experience. In conclusion, a higher level of nature-relatedness can lead to a stronger flow experience, which in turn can increase positive environmental behavior, environmental sensitivity, and communication with nature.